Significance of levels of serum proteins and serum lipids as prognostic indicators in mortality of burn patients - Pruthviraj CS; Gaharwar APS; Saxena, Saurabh; Guru, Aayushi; Dhakad, Sachin; Deepak, Kumar; M, Anaswara (Asian Journal of Medical Sciences, 2023)
Background: Burn mortality is significant because of the higher metabolic and physiological abnormalities; it causes more so than because of the actual injury. Since these abnormalities persist throughout the clinical course of burns, it is believed that both the trend of change and absolute values of the serum proteins and serum lipids have an impact on the prognosis and outcome. Aims and Objectives: This study aimed to find whether serum albumin, globulin, total protein, cholesterol, and triglyceride levels are clinically relevant to determine the mortality of a burn patient and thereby the patient’s outcome. Materials and Methods: The current prospective analytical study was carried out in patients who were admitted to the burn unit, Department of Surgery, Shyam Shah Medical College, and associated Sanjay Gandhi Memorial Hospital, Rewa (M.P.), during the period of April 1, 2021–June 30, 2022 (15 months), and the results were analyzed. Results: In the present study, a total of 112 patients were studied and followed up. Among them, 86% (96/112) of total patients were survivors who were discharged/DOR in stable condition and 14% (16/112) of total patients expired during the course of treatment. It could be statistically inferred that the increase in values of albumin, globulin, total protein, and cholesterol during the clinical course reduces mortality with serum albumin acting as the best predictor with the highest sensitivity of 100% and specificity of 100% and cholesterol the least. Conclusion: It could be statistically inferred that the increase in values of albumin, globulin, total protein, and cholesterol during the clinical course reduces mortality with serum albumin acting as the best predictor and cholesterol the least.